Parametric logarithmic type image processing for contrast based auto-focus in extreme lighting conditions - Florea, Corneliu; Florea, Laura (Zielona Góra: Uniwersytet Zielonogórski)
While most of state-of-the-art image processing techniques were built under the so-called classical linear image processing, an alternative that presents superior behavior for specific applications comes in the form of Logarithmic Type Image Processing (LTIP). This refers to mathematical models constructed for the representation and processing of gray tones images.
Keywords: logarithmic image processing; digital camera; auto-focus